Optimization of multi gating system for the experimental investigation inflow parameters with effects of design in small scale industries. (2022) - Rajkumar, I.; Rajini, N.; Nair, Anish; Prasath, K. Arun; Ramaganesh, M.; Kharrthikeyan, G.R.
Abstract: Most of the automobile components are manufactured only in the casting process. The flow of molten metal plays a major role in sand casting quality. But most of the small-scale industries are predicting the flow path in the trial and error method, it is west of the material and time taking process. Therefore in this research identified different types of gating systems namely Side Sprue Parallel Connection (SSPC) and Centre Sprue Parallel Connection (CSPC) through experimental investigations of the geometric model. To analyze the parameters of velocity, volume, and discharge through gates with the source of water medium. Because the findings derived from this study can be relevant to some other metal with comparable kinematic water viscosity. Data were registered when various gates were closed in different periods. Thanks to the equidistant structure the consistent movement of fluid was accomplished in the cavity. The analysis of variance ANOVA optimization technique is used to identify the better results for chosen two types of the gating system. The observation of water flows through a transparent multi-gate system in a horizontal modular and the total time required for optimizing a design for a given casting. The better discharge and time were seen 66 cm 3 /s at 2.21 s for the CSPC gating system. This type of CSPC gating system setup is used for small-scale industries flow of liquids in useful applications.